2021
DOI: 10.1073/pnas.2104624118
|View full text |Cite
|
Sign up to set email alerts
|

Single-particle diffusional fingerprinting: A machine-learning framework for quantitative analysis of heterogeneous diffusion

Abstract: Single-particle tracking (SPT) is a key tool for quantitative analysis of dynamic biological processes and has provided unprecedented insights into a wide range of systems such as receptor localization, enzyme propulsion, bacteria motility, and drug nanocarrier delivery. The inherently complex diffusion in such biological systems can vary drastically both in time and across systems, consequently imposing considerable analytical challenges, and currently requires an a priori knowledge of the system. Here we int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 64 publications
(86 reference statements)
0
72
0
Order By: Relevance
“…To extract growth rate kinetics for each individual aggregate, we identified points belonging to the growing aggregate with an approximate Euclidean Minimum Spanning tree segmentation 38 and estimated the area using a gaussian mixture model, based on hierarchical clustering in Fig. 3c and 3d (see Supplementary information for the details) [23][24][25][26] . For isotropic morphologies a single linear growth rate is observed (rx), while for anisotropic morphologies the growth curve consists of two rate components (r1 and r2), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To extract growth rate kinetics for each individual aggregate, we identified points belonging to the growing aggregate with an approximate Euclidean Minimum Spanning tree segmentation 38 and estimated the area using a gaussian mixture model, based on hierarchical clustering in Fig. 3c and 3d (see Supplementary information for the details) [23][24][25][26] . For isotropic morphologies a single linear growth rate is observed (rx), while for anisotropic morphologies the growth curve consists of two rate components (r1 and r2), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the 3D dSTORM data, the direct observation of HI spherulite growth by REPLOM confirmed that HI spherulites grow both anisotropically and isotropically (Figure 3). To extract the growth rate kinetics for each individual aggregate, we identified the points belonging to the growing aggregate with an approximate Euclidean Minimum Spanning tree segmentation (Cowan & Ivezić, 2008) and estimated the area using a Gaussian mixture model based on hierarchical clustering in Figure 3c and 3d (see Supporting Information for the details) (Jensen et al, 2021; Pinholt et al, 2021; Stella et al, 2018; J. Thomsen et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Attaining real-time videos of the spherulite growth process allowed to reconstruct the super-resolution images of the spherulites and their growth kinetics. Using homemade software based on Euclidian minimum spanning tree and machine learning clustering [27][28][29][30][31] , we quantitatively associated the growth rates to specific morphological transitions during growth, eventually extracting detailed energy barriers and, thus, the energy landscape for each type of aggregation morphology. Our data on astigmatism-based 3D direct stochastic optical reconstruction microscopy (dSTORM) 32 , spinning disk confocal microscopy 33 , and scanning electron microscopy (SEM) confirm that the presence of heterogeneous structures is not artefact of our method.…”
Section: Introductionmentioning
confidence: 99%